Pengembangan Paving Block Berbasis Fitorimediasi sebagai Solusi Mitigasi Banjir Perkotaan - Muhammad Ramadhani Rahman; Kurnia Putri Dinanti; Nabila Maulidia Fatahillah; Ahmad Zaidan Wahab; Sendi Hendiawan Prayogo (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The problem of urban flooding is a growing issue due to high population density, increasing volumes of plastic waste, and the reduction of water absorption areas. The use of conventional paving blocks, which are impermeable, further exacerbates flooding conditions because they do not allow water to infiltrate into the soil. This study aims to develop an innovative plastic waste-based paving block incorporating rice straw and sugarcane bagasse, along with the integration of phytoremediation concepts as a solution for urban flood mitigation. The method employed was an experimental approach involving the following stages: material preparation, plastic incineration, material mixing, molding, and testing of water absorption capacity and compressive strength. The results showed that paving blocks with a combination of plastic waste, rice straw, and sugarcane bagasse had the highest water absorption rate of 34% and compressive strength of 21 kg/cm², meeting SNI standards. The addition of natural materials containing silica was proven to enhance the material’s porosity and strength. Additionally, the application of phytoremediation using water hyacinth has the potential to improve the quality of water seeping into the soil. Thus, this phytoremediation-based paving block innovation can serve as an effective alternative solution to reduce flood risks while supporting sustainable waste management and environmental stewardship.